Necrotising otitis externa and how to reduce length of hospital stay: a complete audit cycle of 77 hospital admissions. Issue 7 (22nd July 2022) - Mohammed, H; Chean Khun Ng, J; Qureshi, M H; Yates, P
Abstract: Background: Necrotising otitis externa is a serious condition that requires hospital admission. Longer hospital stays are associated with increased complications. Method: This was a closed audit cycle in a tertiary ENT centre of patients presenting with necrotising otitis externa to the ENT department between 2015 and 2019. The aim was to audit the length of hospital stay in comparison to national figures as well as the time needed for investigations. Results: The number of patients with necrotising otitis externa is increasing in England. Length of stay, however, appears to be more stable. A total of 66 admissions occurred over the study period for 48 patients in total, and mean length of stay was 12.4 days. After implementation of a new protocol, length of stay was reduced to 7.1 days. Conclusion: Patients with necrotising otitis externa require prompt diagnosis and management in order to shorten length of stay in hospital and avoid serious complications. Multi-disciplinary protocol development and implementation could help in reducing length of stay of necrotising otitis externa patients.